PLANNING FOR PROFITS–HOW SOME EXECUTIVES ARE DOING IT. - Hay, Leon E. (The Accounting Review, 1960)
Abstract The article focuses on the concept of profit planning. Business profits can ye planned with a reasonable degree of success. The objective of profit plan is to maximize the long run financial health of the enterprise. Profit planning implies the predetermination of objectives and the preparation of plans to meet those objectives. Budgeting often involves only a representation of what the results will be if present plans and policies are carried out in the forecasted economic climate. Profit planning, like budgeting, extends to all phases of producing, selling, and financing activity for the coming period and it anticipates needs beyond operations for the coming period through means of the capital expenditures plan. A very popular means for expressing the financial objectives of profit-seeking businesses is the return on investment. Profit planning involves setting long range corporate objective, and determining means of achieving them. A very popular means for expressing the financial objectives of profit-seeking businesses is the return on investment.